2011
DOI: 10.1098/rspb.2011.0239
|View full text |Cite
|
Sign up to set email alerts
|

Plant genotypic diversity increases population size of a herbivorous insect

Abstract: It is critical to incorporate the process of population dynamics into community genetics studies to identify the mechanisms of the linkage between host plant genetics and associated communities. We studied the effects of plant genotypic diversity of tall goldenrod Solidago altissima on the population dynamics of the aphid Uroleucon nigrotuberculatum. We found genotypic variation in plant resistance to the aphid in our experiments. To determine the impact of plant genotypic diversity on aphid population dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 43 publications
2
66
0
Order By: Relevance
“…For example, in the most detailed study to date regarding the population response of herbivores to plant genotypic diversity, movement among plants was hypothesized to be a major driver of aphid population growth [12]. Compensatory feeding can occur when animals are restricted to diets suboptimal for their target intake of different nutrients, such as suboptimal protein : carbohydrate ratios [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the most detailed study to date regarding the population response of herbivores to plant genotypic diversity, movement among plants was hypothesized to be a major driver of aphid population growth [12]. Compensatory feeding can occur when animals are restricted to diets suboptimal for their target intake of different nutrients, such as suboptimal protein : carbohydrate ratios [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, a growing body of literature suggests that genotypic diversity within species can have pronounced consequences on populations, communities and ecosystems [8]. However, while several studies have now shown that plant genotypic diversity typically increases the abundance of herbivores [9][10][11][12], how changes in herbivore abundance are linked to the consumption of plant resources remains unknown [13,14]-an important gap in our understanding of how plant diversity alters energy transfer across trophic levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on plant intra-and interspecific diversity have focused exclusively on the bottom-up effects of plant diversity within a single trophic level (herbivores; [8,9]), but plant diversity may also directly or indirectly affect the third trophic level, i.e. enemies and mutualists of herbivores (see [3,4,10], and the scheme represented in figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have shown that plant genotypes influence plant-arthropod interactions and community properties of plant-associated arthropods, including abundance, species richness, and species composition (Johnson and Agrawal 2005;Wimp et al 2005;Bailey et al 2006;Bangert et al 2006;Whitham et al 2006;Barbour et al 2009;Utsumi et al 2011). Both the induced plant responses and plant genetic variations are likely to have qualitatively similar effects on structuring plant-associated arthropod communities (McGuire and Johnson 2006;Utsumi et al 2009b).…”
Section: Sources Of Plant Trait Variation and Structuring Arthropod Cmentioning
confidence: 99%